The Effect of Brand Awareness "Word Of Mouth" and Perception of Risk on the Buying Intention towards Box Brand GIVI in Surabaya - Luhung Diwangkoro; Jiwangga Hadi Nata (TIJAB (The International Journal of Applied Business), 2017)
The purpose of this study was to discuss the influence of Brand Awareness, word of mouth, and the perception of the tendency towards GIVI purchase intention in Surabaya. This research is a quantitative research with survey method. Sources of data obtained from questionnaires collected with a Likert scale and the results were analyzed by multiple linear regression methods. The results of the study prove that brand awareness gets 2,050 tcts supported by the significance of 0,044 (p <0,05) Word of mouth gets t count 2,064 supported by the significance of 0,043 (p <0,05) so that word of mouth has a significant effect on purchase intention. The perception of risk gets t count of -3.018 supported by significance of 0.004 (p <0.05) Brand awareness, word of mouth, and risk perceptions have the same significance for purchasing compatibility because the Fcount is 52.255 with a significant value of 0.000 (p <0 05). The R square coefficient is 0.714 then the variation of changes that occur in the dependent variable 71.4% which can be accessed jointly by the independent variable and the remaining 28.6% by other variables outside the three independent variables used in this study.